Leveraging Information Technology for Indonesia Agribusiness Global Market Competitiveness - Muhamad Ivan Fadilah; Khalisha Alifia Zahra (Penerbit Goodwood, 2025)
Purpose: To systematically review existing literature on how the utilization of information technology can enhance the global market competitiveness of Indonesian agribusiness products. Methodology/approach: This study employs a Systematic Literature Review (SLR) method, following the PRISMA protocol. Relevant articles published between 2021-2025 were identified and selected from academic databases including IEEE Xplore, ScienceDirect, and Emerald Insight, followed by a qualitative thematic synthesis of the final 30 included studies. Results/findings: The analysis reveals that technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), and digital e-commerce platforms significantly impact competitiveness. Their adoption is proven to enhance supply chain efficiency and resilience, expand market access for small-scale farmers and MSMEs, and improve overall product quality and transparency. Conclutions: Information technology is a critical strategic enabler for transforming Indonesian agribusiness. However, its widespread adoption is still hampered by a complex network of economic, infrastructural, human resource, and institutional barriers that require integrated and holistic solutions. Limitations: This review is limited to published and academically accessible literature. Consequently, it may not capture innovative, on-the-ground practices that have not yet been formally documented in scientific articles. Contribution: This study provides a strategic framework that can guide Indonesian policymakers in formulating integrated policies for digital transformation, including infrastructure development and digital literacy programs. For agribusiness actors, it highlights the importance of investing in technology and upskilling human resources to strengthen their global position